2008
DOI: 10.1192/bjp.bp.107.039164
|View full text |Cite
|
Sign up to set email alerts
|

Late-life depression and mortality: influence of gender and antidepressant use

Abstract: The association between depression and mortality is gender-dependent and varies according to symptom load and antidepressant use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
4
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 28 publications
3
71
4
2
Order By: Relevance
“…In men with Severe DS, we did not observe a significant association with any of the disability measures after 7 years of follow-up, probably due to lower number (4.9% compared to 12.2% for women) and a higher mortality rate. Indeed in the same cohort, an increase in depression-related 4-year mortality risk was observed in men with mild (OR=2.8) and treated severe DS (OR=5.3) whereas in women only non-treated severe DS which slightly increased risk (OR=1.8) (Ryan et al, 2008). Several previous studies have reported an increase in activity limitations (most frequently severe ADL limitations) associated with DS in elderly community cohorts (see (Carriere et al, 2009;Schillerstrom et al, 2008), for reviews).…”
Section: Gender Differences In Depression-related Activity Limitationmentioning
confidence: 80%
See 2 more Smart Citations
“…In men with Severe DS, we did not observe a significant association with any of the disability measures after 7 years of follow-up, probably due to lower number (4.9% compared to 12.2% for women) and a higher mortality rate. Indeed in the same cohort, an increase in depression-related 4-year mortality risk was observed in men with mild (OR=2.8) and treated severe DS (OR=5.3) whereas in women only non-treated severe DS which slightly increased risk (OR=1.8) (Ryan et al, 2008). Several previous studies have reported an increase in activity limitations (most frequently severe ADL limitations) associated with DS in elderly community cohorts (see (Carriere et al, 2009;Schillerstrom et al, 2008), for reviews).…”
Section: Gender Differences In Depression-related Activity Limitationmentioning
confidence: 80%
“…Severity of depressive symptoms was assessed using the 20-item Center for Epidemiologic Studies-Depression scale (CES-D) (Radloff, 1977). For this analysis, participants were classified into one of three groups (Ryan et al, 2008). 'Severe depressive symptomatology' (Severe DS group) included participants with a current MDE or a CES-D score of 23 or over (allowing for the fact that some participants with severe symptoms did not reach DSM classification criteria, principally because of the duration of symptoms).…”
Section: Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the exact pathways leading from depression to increased mortality are not yet known, a broad range of differential pathways between men and women may explain these differences (Penninx et al, 1999;Ryan et al, 2008). For example, the physiological and behavioral reactions to stress of women may differ from those of men (Penninx et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Here, the exclusion of participants who committed suicide from the analyses did not change the results (data not shown). Moreover, a number of studies have reported an increased risk of mortality in depressed men, but not in women [19,20]. A meta-analysis including studies with random samples from different communities found that the relative mortality risk for depressed men was only non-significantly higher than for depressed women [11].…”
Section: Discussionmentioning
confidence: 99%